Structural Reforms, IMF Programs and Capacity Building : An Empirical Investigation - Arezki, Rabah (IMF Working Papers; Working Paper ;, 2012)
This paper investigates the role that International Monetary Fund (IMF) programs and capacity building play in fostering structural reforms. To do so, we exploit two novel datasets on IMF capacity building and structural reforms available for over one hundred IMF member countries over the period 1980 - 2010. The main results are threefold. First, there is a general association between IMF programs and structural reforms but this relationship is not very robust. Second, IMF training leads to an increase in structural reforms but only through IMF programs and only when a significant share of public servants is trained. Third, IMF technical assistance does not significantly lead to more structural reforms but raises the likelihood of completion of ongoing IMF programs. Our results are robust to a large number of checks, estimators and correcting for endogeneity.